Face Mask Use in the Community for Reducing the Spread of COVID-19: A Systematic Review - Coclite, Daniela; Napoletano, Antonello; Gianola, Silvia; del Monaco, Andrea; D'Angelo, Daniela; Fauci, Alice; Iacorossi, Laura; Latina, Roberto; Torre, Giuseppe La; Mastroianni, Claudio M.; Renzi, Cristina; Castellini, Greta; et al. (Frontiers in Medicine, 2021)
Background: Evidence is needed on the effectiveness of wearing face masks in the community to prevent SARS-CoV-2 transmission. Methods: Systematic review and meta-analysis to investigate the efficacy and effectiveness of face mask use in a community setting and to predict the effectiveness of wearing a mask. We searched MEDLINE, EMBASE, SCISEARCH, The Cochrane Library and pre-prints from inception to 22 April 2020 without restriction by language. We rated the certainty of evidence according to Cochrane and GRADE approach. Findings: Our search identified 35 studies, including 3 randomised controlled trials (RCTs) (4017 patients), 10 comparative studies (18984 patients), 13 predictive models, 9 laboratory experimental studies. For reducing infection rates, the estimates of cluster-RCTs were in favour of wearing face masks versus no mask, but not at statistically significant levels (adjusted OR 0.90, 95%CI 0.78-1.05). Similar findings were reported in observational studies. Mathematical models indicated an important decrease in mortality when the population mask coverage is near-universal, regardless of mask efficacy. In the best-case scenario, when the mask efficacy is at 95%, the R0 can fall to 0.99 from an initial value of 16.90. Levels of mask filtration efficiency were heterogeneous, depending on the materials used (surgical mask: 45-97%). One laboratory study suggested a viral load reduction of 0.25 (95%CI 0.09-0.67) in favour of mask versus no mask. Interpretation: The findings of this systematic review and meta-analysis support the use of face masks in a community setting. Robust randomised trials on face mask effectiveness are needed to inform evidence-based policies. Funding: none. PROSPERO registration: CRD42020184963.